Genetic analysis of Iranian and Turkish red foxes (Vulpes vulpes) based on mitochondrial DNA (D-loop) sequences. Issue 6 (2nd November 2019) - Telcİoğlu, Murat and İbİş, Osman and Aksöyek, Eren and Özcan, Servet and Moradİ, Mohammad and; an, Ömer Fİkret and Tez, Coşkun
Abstract : Red fox ( Vulpes vulpes ) is known as a medium-sized game species in some parts of the Northern Hemisphere and a predator therewithal. In this study, we focused on Iranian (n = 14) and Turkish (n = 54) red foxes. Genetic analyses were performed by using mitochondrial D-loop sequences and revealed that there was a remarkable genetic variation within the Iranian and the Turkish populations. Intraspecific pairwise divergences within the Iranian and the Turkish red foxes ranged from 0.2% to 4% and from 0.3% to 3.1%, including 10 and 25 haplotypes, respectively. Also, a haplotype network was reconstructed by using the D-loop sequences obtained from the current study and conspecific populations throughout the species' range. Based on the D-loop sequences, the red foxes were clustered into three main haplogroups (Palearctic basal haplotypes–African clade, Holarctic clade, Nearctic clade), in which the Iranian and the Turkish red foxes were grouped into two haplogroups (Palearctic basal haplotypes–African clade and Holarctic clade). The present study proposed that genetic differentiation occurs within the Iranian and the Turkish populations of the red fox, and it supported an ancient Middle Eastern–North African origin suggested by previous studies for modern red foxes due to the occurrence of some the Iranian and the Turkish haplotypes that were grouped into the Palearctic basal haplotypes–African clade.